Development of Peptide Targeted PLGA-PEGylated Nanoparticles Loading Licochalcone-A for Ocular Inflammation - Ruth Galindo; Elena Sánchez-López; María José Gómara; Marta Espina; Miren Ettcheto; Amanda Cano; Isabel Haro; Antoni Camins; María Luisa García (MDPI AG, 2022)
Licochalcone-A is a natural compound with anti-inflammatory properties. However, it possesses low water solubility, making its application for the treatment of ocular inflammation difficult. To overcome this drawback, biodegradable nanoparticles incorporating Licochalcone-A have been developed. Additionally, to avoid fast clearance and increase cellular internalization into the ocular tissues, PLGA nanoparticles have been functionalized using PEG and cell penetrating peptides (Tet-1 and B6). To optimize the formulations, a factorial design was carried out and short-term stability of the nanoparticles was studied. Moreover, morphology was also observed by transmission electron microcopy and in vitro drug release was carried out. Ocular tolerance of the formulations was ensured in vitro and in vivo and anti-inflammatory therapeutic efficacy was also assessed. Surface functionalized nanoparticles loading Licochalcone-A were developed with an average size below 200 nm, a positive surface charge, and a monodisperse population. The formulations were non-irritant and showed a prolonged Licochalcone-A release. Despite the fact that both Licochalcone-A Tet-1 and B6 functionalized nanoparticles demonstrated to be suitable for the treatment of ocular inflammation, B6 targeted nanoparticles provided greater therapeutic efficacy in in vivo assays.